Improving practice through collaboration: Early experiences from the multi-site Spinal Cord Injury Implementation and Evaluation Quality Care Consortium. (30th September 2021) - Bateman, Emma A.; Sreenivasan, Vidya A.; Farahani, Farnoosh; Casemore, Sheila; Chase, Andrea D.; Duley, Jennifer; Evbuomwan, Ivie K.; Flett, Heather M.; Ventre, Anellina; Craven, B. Catharine; Wolfe, Dalton L.
Abstract : Context: Dedicated implementation efforts are critical to bridging the gaps between current practices and best practices. A quality improvement collaborative (QIC), the Spinal Cord Injury Implementation and Evaluation Quality Care Consortium (SCI IEQCC), was established to meet this need, bringing together a network of clinicians and administrators to systematically improve the quality and equity of tertiary spinal cord injury or disease (SCI/D) rehabilitation care in Ontario, Canada. Methods: Clinicians and leaders from five tertiary SCI/D rehabilitation centers and two not-for-profit SCI/D advocacy groups comprised a network dedicated to supporting implementation of the SCI-High quality indicators in prioritized domains of SCI rehabilitation and related best practices by: (1) building capacity through implementation science education of frontline clinicians; (2) providing resources and support to empower frontline clinicians to lead quality improvement efforts within their institutions; (3) promoting wider learning through a network for sharing ideas, efforts, and experiences; and (4) collecting indicator data to facilitate provincial evaluation of goal attainment. Results: Network members and sites collaborated to implement best practices within six priority domains; in 18 months, significant progress has been made in emotional wellbeing, sexual health, walking, and wheeled mobility despite disruptions due to the COVID-19 pandemic. These efforts encompass heterogeneous challenges and strategies, ranging from developing clinical skills programs, to streamlining processes, to manipulating physical space. Conclusion: A QIC targeting SCI/D rehabilitation demonstrates promise for advancing the implementation of best practices, building implementation science capacity across multiple sites, and for promoting collaboration amongst SCI/D rehabilitation centers and organizational partners.